What form of visibility affects earnings management? Evidence from Italian family and non-family firms - Giovanna Gavana; Pietro Gottardo; Anna Maria Moisello (Administrative Sciences, 2019)
This paper addresses the issue of financial communication quality by studying the determinants of earnings management practices in family and non-family businesses. Previous literature has highlighted the effect of a company's size, as a form of visibility, on earnings management practices. This study focuses on the analysis of the relationship between different forms of visibility-exposure to financial press, proximity to the consumer, size of assets, sales and firm age-and earnings quality. The results show that the forms of visibility taken into consideration have a different effect on earnings management practices. Furthermore, they show that family businesses are less likely to resort to these unethical practices, especially in the presence of financial press exposure and proximity of the business to the consumer.
Keywords: 350; earnings management; family firms; visibility